Análise experimental da influência do ar condicionado automotivo nas emissões e no consumo de combustível em veículos leves considerando o ciclo urbano (FTP-75) - Iolanda de Lourdes Goncalves Dias (2017)
Automotive air conditioning is the accessory that accounts for the largest increase in fuel consumption in a car consequently, the greatest increase in CO2 emissions into the atmosphere. The difference between fuel consumption values obtained in Emission Laboratories and real world conditions is increasing and one of the factors that justify is the growth of the sales of vehicles equipped with air conditioning. In Brazil, the emissions tests are performed with the air conditioning off. Due to higher fuel consumption in vehicles with air conditioning turned on, the test procedure described in ABNT NBR 6601 has considered that when more than 33% of vehicles of the same brand, model, engine and transmission that are originally equipped with air conditioning the coefficients of the resistive force equation must be increased by 10%. The objective of this work was to verify the behavior of the fuel consumption of two vehicles equipped with AC through laboratory tests, considering FTP-75 in three different conditions, to evaluate if the increase of 10% is a good estimation of the air conditioning turned on. The increase in fuel consumption was 15% to 19% with the air conditioning turned on, against only 3% for tests with an increase of 10% on the coefficients of the equation of resistive forces. The results show that the NOx and CO emissions values with automotive air conditioning on do not exceed the limits of PROCONVE's L-6 phase. With the results obtained, it can be verified that the attempt of ABNT NBR 6601 to consider an influence of the air conditioning in the FTP-75 cycle is not enough to guarantee fuel consumption values close to the real impact of the equipment on the cars tested in this work